2014
DOI: 10.13080/z-a.2014.101.001
|View full text |Cite
|
Sign up to set email alerts
|

Potassium leaching from Endocalcari-Endohypogleyic Cambisol as influenced by precipitation rate and crop management

Abstract: The aim of this research was to compare a few crop management systems in respect of potassium leaching in order to reduce the leaching losses. Research was carried out on an Endocalcari-Endohypogleyic Cambisol (CMg-n-wcan) at the experimental site of Lithuanian Institute of Agriculture (currently -Institute of Agriculture, Lithuanian Research Centre for Agriculture and Forestry). The focus was on the search for factors responsible for leaching, including precipitation amount and rate, and selected soil propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, other work has found that K‐saturated soils boast larger aggregates of greater stability, compared to soils saturated with divalent cations (Bronick & Lal, 2005). In normal and wet years, it has been found that K + leaching is positively influenced by the application rate of K fertilizers and the content of less than 0.25 mm soil aggregates in the topsoil (Bučienė et al, 2014). It is plausible that K + has the ability to strengthen aggregate stability through weakening electrostatic repulsion between soil particles through polarization (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, other work has found that K‐saturated soils boast larger aggregates of greater stability, compared to soils saturated with divalent cations (Bronick & Lal, 2005). In normal and wet years, it has been found that K + leaching is positively influenced by the application rate of K fertilizers and the content of less than 0.25 mm soil aggregates in the topsoil (Bučienė et al, 2014). It is plausible that K + has the ability to strengthen aggregate stability through weakening electrostatic repulsion between soil particles through polarization (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As was showed by Kayser and Isselstein (2005), high levels of available K in the soil and large quantities of fertilizers may increase K losses significantly. Bučienė et al (2014) found that K leaching increases with the higher rate of soil aggregates <0.25 mm and humus in topsoil.…”
Section: Introductionmentioning
confidence: 94%